Numerical simulation of R410A condensation in horizontal microfin tubes. (16th February 2017) - Zhang, Jingzhi; Li, Wei; Minkowycz, W. J.
ABSTRACT: The heat transfer characteristics of condensation for R410A inside horizontal microfin tubes with 0° and 18° helical angles were investigated numerically. The numerical data fit well with the experimental results and with the empirical correlations. The results indicate that local heat transfer coefficients increase with increasing mass flux, vapor quality, and helical angle. The heat transfer enhancement in the helical microfin tubes is more pronounced at higher mass flux and vapor quality. The centrifugal force induced by the microfin with a 18° helical angle tends to spread the liquid from the bottom to the top, leading to a nearly symmetrical liquid–vapor interface during condensation. Swirling flows in the liquid phase are observed in the tube with the 18° helical angle, but the liquid phase tends to flow to the bottom due to gravity in the tube with the 0° helical angle.